A new improvement on a chemical kinetic model of primary reference fuel for multi-dimensional CFD simulation. (1st February 2016) - Zhen, Xudong; Wang, Yang; Liu, Daming
Highlights: A new optimized chemical kinetic mechanism for PRF is developed. New mechanism optimization is performed based on the CHEMKIN simulations. More reactions of C0 –C1 oxidation are added in the present mechanism. Good performance is achieved of mechanism by validating various reactors and operating conditions. Abstract: In the present study, for the multi-dimensional CFD (computational fluid dynamics) combustion simulations of internal combustion engines, a new optimized chemical kinetic reaction mechanism for the oxidation of PRF (primary reference fuel) instead of gasoline has been developed. In order to carry out the in-depth research for combustion phenomenon of internal combustion engines, an optimized reduced PRF mechanism including more intermediate species and radicals was developed. The developed mechanism contains of iso-octane (C8 H18 ) and n-heptane (C7 H16 ) surrogates, which contains of 51-species and 193 reactions. Compared with many other mechanisms of PRF, more reactions of C0 –C1 oxidation (100 reactions) are added in the present mechanism. In order to improve the performances of the model, the developed mechanism focused on the improvement through the prediction of the ignition delay time. The developed mechanism has been validated against various experimental and simulation data including shock tube data, laminar flame speed data and HCCI (homogeneous charge compression ignition) engine data. The results showed that the developed PRF mechanism was agreements with the experimental data and other approved reduced mechanisms, and it could be applied to the multi-dimensional CFD simulations for internal combustion engines.